Comparison of Superovulated Embryo Quality in Simmental Cattle Inseminated with 0 °C-Refrigerated and Liquid Nitrogen-Frozen Semen - Jie-Ru Wang; Fei Huang; Peng Niu; Hong Cheng; Hui-Min Qu; Xiao-Peng Li; Xue-Yan Wang; Jie Wang; Jia-Jia Suo; Di Fang; Qing-Hua Gao (Biology, 2025)
Semen quality plays a crucial role in bovine in vivo embryo production. This study aimed to compare the effects of 0 °C-refrigerated semen and liquid nitrogen-frozen semen on embryo quality in Simmental cattle. Semen collected from five bulls was equally divided into two groups: one diluted with a 0 °C refrigeration solution and stored at 0 °C, and the other diluted with a cryopreservation solution and stored in liquid nitrogen for 24 h. We evaluated sperm motility, progressive motility (assessed via a computer-assisted sperm analyzer), acrosome integrity, and plasma membrane integrity in both groups. Fifty superovulated Simmental cows were artificially inseminated with semen from both groups. Embryos were non-surgically flushed on day seven, followed by BrdU proliferation staining and TUNEL apoptosis staining. Proliferation and apoptosis levels were quantified using marker genes. Results showed that 0 °C-refrigerated semen exhibited significantly higher sperm motility, progressive motility, acrosome integrity, and plasma membrane integrity compared to liquid nitrogen-frozen semen (p < 0.05). While total embryo numbers showed no significant difference between groups (p ≥ 0.05), embryos from 0 °C-refrigerated semen contained significantly more proliferative cells (p < 0.05) and fewer apoptotic cells (p < 0.05) than those from frozen semen. These findings demonstrate that 0 °C-refrigerated semen outperforms liquid nitrogen-frozen semen in both sperm quality parameters and resultant embryo quality.